2000
DOI: 10.1007/s001340000791
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase activity and blood glutathione redox ratio in infants and children with septic shock syndrome

Abstract: Potent and simultaneous activation of the two redox systems strongly indicates a definite role of free radicals from XO in the overspill of the acute proinflammatory reaction of the shock syndrome, followed by a significant downregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
(42 reference statements)
2
33
0
Order By: Relevance
“…Increased xanthine oxidase activity has been reported in patients with sepsis or SIRS in both the adult [63] and pediatric [70,71] populations. Galley et al [63] found xanthine oxidase activation and increased free radical concentrations in septic patients compared with both healthy volunteers and noninfected patients.…”
Section: Oxidative Stress and Sepsismentioning
confidence: 97%
“…Increased xanthine oxidase activity has been reported in patients with sepsis or SIRS in both the adult [63] and pediatric [70,71] populations. Galley et al [63] found xanthine oxidase activation and increased free radical concentrations in septic patients compared with both healthy volunteers and noninfected patients.…”
Section: Oxidative Stress and Sepsismentioning
confidence: 97%
“…In animal models, endotoxemia is known to lower GSH levels in the liver (Jaeschke, 1992;Payabvash et al, 2006) and in peritoneal macrophages and lymphocytes (Victor and De La Fuente, 2003). This occurs also in patients hospitalized for sepsis as lower blood GSH:GSSG ratios have been reported (Németh and Boda, 2001). Exogenous GSH suppressed LPS-induced systemic inflammatory response and reduced mortality (Sun et al, 2006).…”
Section: Endotoxemiamentioning
confidence: 99%
“…If birth is marked by a period of ischemia followed by reoxygenation (e.g. asphyxia), ROS formation is further augmented through the hypoxanthine-xanthine oxidase pathway (1,2). In addition, preterm infants are frequently exposed to ventilation with high concentrations of oxygen, further adding up to this ROS formation (3).…”
mentioning
confidence: 99%